Moderation Process For Valid Mathematics Teacher-Made Test Results: Evidence of Final National Performance in Secondary Schools in Zanzibar - Haji, Hassan A.; Salema, Dr. Victorini; Siamoo, Dr. Peter (International Journal of Scientific Research and Management (IJSRM), 2025)
This study assessed the moderation process for valid Mathematics teacher-made test (TMT) results and their implications for national performance in secondary schools in Zanzibar. Grounded in Classical Test Theory (Novick, 1968), the study employed a convergent design under a mixed-methods approach. The target population included 3,768 individuals from 30 public schools, including students, heads of schools, Mathematics teachers, and ZEC subject coordinators. A sample of 436 respondents was selected using purposive and proportionate stratified random sampling techniques. Data collection instruments included interview guides, document analysis guides, and questionnaires. Instrument validity was confirmed by three education research experts who supervise postgraduate students from MWECAU. At the same time, reliability was assessed using the Cronbach Alpha method (r = 0.774 for teacher questionnaires and r = 0.759 for student questionnaires). Ethical guidelines were strictly followed throughout the research. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were subjected to thematic analysis. The findings revealed a significant gap between teachers' perceptions (high extent) and students' (moderate extent) about quality of test Moderated to enhance students Mathematics performance. The finding of the hypothesis testing reveals low credibility of Mathematics TMT in enhancing students' academic achievement, indicating a need for improving moderation process, assessment procedures and teacher training to align TMT with National Examinations Standards. However, interviews and document reviews highlighted inadequacies in moderation and potential grading biases. These findings underscore the need for improving TMT to support students in teaching and learning to enhance students' performance in Mathematics in FTNE. The study concludes that enhanced communication and greater teacher involvement in moderation are essential for fair and reliable assessments. It recommends the implementation of structured moderation processes and the promotion of open communication to improve the effectiveness of Mathematics TMTs and support student success in FTNA.